2018
DOI: 10.1111/imig.12535
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Native‐Migrant Differences in Parental Knowledge about the German Educational System

Abstract: To make sound educational decisions, students and their parents have to be informed about the way the educational system works. Such knowledge, however, tends to vary across social groups. This study investigates the differences in education‐related knowledge between native and migrant mothers in the German context. Empirical analyses based on a sample of native German mothers and mothers from Turkey or the former Soviet Union (N = 2076) indicate that migrant mothers know less about the German educational syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Familiarity with educational alternatives can have two different facets. On the one hand, it involves objective knowledge about certain educational alternatives and the prerequisites associated with them (e.g., Kao & Tienda, 1998;Kretschmer, 2019;Olczyk & Will, 2019). On the other hand, however, this measurement also includes a subjective component that goes beyond objective knowledge and may include an internalization of values and behaviours.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Familiarity with educational alternatives can have two different facets. On the one hand, it involves objective knowledge about certain educational alternatives and the prerequisites associated with them (e.g., Kao & Tienda, 1998;Kretschmer, 2019;Olczyk & Will, 2019). On the other hand, however, this measurement also includes a subjective component that goes beyond objective knowledge and may include an internalization of values and behaviours.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Thus, they prepare themselves to a lesser extent for the demands of the labor market. Information deficits regarding the peculiarities of the labor market (Kretschmer 2019) may exacerbate this phenomenon. Accordingly, Nennstiel (2021) has shown that immigrants begin their search for a vocational training position later than majority school graduates.…”
Section: Search Behaviormentioning
confidence: 99%
“…Concerning structural integration, late adolescence is a time in which youth make important decisions on their educational careers or even enter the labor market. Social capital affects these decisions, and since most Muslim youth are descendants of immigrants, some of them may lack knowledge of the educational system and labor market institutions (Kretschmer 2019). Contact to native-origin peers whose families are better acquainted with the institutions of the host society thus can be beneficial to make adequate plans (Lancee 2010).…”
Section: Saom Analysismentioning
confidence: 99%